2021
DOI: 10.3390/v13061158
|View full text |Cite
|
Sign up to set email alerts
|

The Current Landscape of Oncolytic Herpes Simplex Viruses as Novel Therapies for Brain Malignancies

Abstract: Despite advances in surgical resection and chemoradiation, high-grade brain tumors continue to be associated with significant morbidity/mortality. Novel therapeutic strategies and approaches are, therefore, desperately needed for patients and their families. Given the success experienced in treating multiple other forms of cancer, immunotherapy and, in particular, immunovirotherapy are at the forefront amongst novel therapeutic strategies that are currently under investigation for incurable brain tumors. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…The detargeting-retargeting approach confers cancer-specificity, albeit not absolute since any given TAA exhibits a limited expression in a few off-tumor tissues [ 10 ]. It differs from the broad group of attenuation strategies, which confer cancer-selectivity and are based on deletion or mutation in virulence genes, including the γ 1 34.5 gene [ 12 ], or in genes that contrast the innate and adaptive immune responses [ 13 , 14 ]. The vast majority of oHSVs in clinical trials, and the approved talimogene laherparepvec (also named OncoVEXGM-CSF) were generated by the latter strategy [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detargeting-retargeting approach confers cancer-specificity, albeit not absolute since any given TAA exhibits a limited expression in a few off-tumor tissues [ 10 ]. It differs from the broad group of attenuation strategies, which confer cancer-selectivity and are based on deletion or mutation in virulence genes, including the γ 1 34.5 gene [ 12 ], or in genes that contrast the innate and adaptive immune responses [ 13 , 14 ]. The vast majority of oHSVs in clinical trials, and the approved talimogene laherparepvec (also named OncoVEXGM-CSF) were generated by the latter strategy [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, HSV1 can cause severe infection of the brain and liver and/or death, however the rQNestin virus has been modified to replicate only in glioma cells but not in normal, healthy cells [ 181 ]. The UL39 gene encoding the viral ribonucleotide reductase large subunit infected cell protein 6 (ICP6) and both endogenous copies of the gamma34.5 gene that encodes for the RL1 neurovirulence protein infected cell protein 34.5 (ICP34.5) (needed for robust viral growth in an infected cell) are deleted, and one copy of the gamma34.5 gene is reinserted under control of a nestin promoter, which is selectively activated in gliomas [ 182 ]. By inactivating UL39, viral ribonucleotide reductase activity is disrupted, resulting in the inhibition of nucleotide metabolism and viral DNA synthesis in non-dividing, healthy cells but not in dividing cells [ 183 ].…”
Section: Applications Of Nanotechnology In Cancer Therapeuticsmentioning
confidence: 99%
“…This is the fourth OV approved worldwide. 5 In addition to the approved OVs, there are currently several OV products that have been tested in phases I–III clinical trials worldwide, from various types of adenoviruses, HSV, coxsackievirus, poxvirus, and reovirus. It has been demonstrated that the cancer cells infected by OVs secrete a large number of cytokines, while the lysed tumor cells release a variety of tumor-associated antigens.…”
Section: Introductionmentioning
confidence: 99%